New Model of Character Education Evaluation Management Information System Based on Google Workspace in Kindergarten - Gustriya Wijayanto; Wahyudi Wahyudi; Sophia Tri Satyawati; Sachin Gupta (Universitas Negeri Semarang, 2024)
Character education is a joint responsibility between schools and parents, especially in the context of a character assessment inside and outside the school environment. The aim of this research and development is to create a character education evaluation information system model based on Google Workspace with a focus on increasing parental participation in assessing children's character. The research method used is Research and Development (R&D) with the application of the ADDIE model and the Mixed Method (sequential exploratory) approach. Respondents to this research involved school principals, teachers and parents. Various data collection techniques such as interviews, observation, FGD, documentation studies, and questionnaires were used in this research. Data collection instruments include interview guidelines, observation guidelines, FGD guidelines, and questionnaires. The data analysis was carried out through qualitative descriptive and quantitative descriptive. The results of this research are the development of a model book and Google Workspace-based character education evaluation website product. The validation by IT experts showed an assessment percentage of 88.61% in the good category, while the character education experts gave an assessment percentage of 84.65% in the good category. The ratings from the users, especially teachers, reached a percentage of 86.09% in the good category, and from the parents it was 76.70% in the good category. Therefore, it can be concluded that the product developed is suitable for use. The products developed can be used and help parents and schools monitor children's character development